Medical Students Learning Styles in Birjand University of Medical Sciences - Saeed Kalbasi; Mohsen Naseri; Gholamreza Sharifzadeh; Ali Poursafar (Kerman University of Medical Sciences, 2008)
Background & Objective : Learning and its improvement are the foundation of all activities in educational systems One of the most important effective factors on students learning is their learning style Being aware of the learning style used by students help teachers to assist the students for a better use of different learning styles On the other hand teachers can change their own educational style according to the students learning style to reach maximum level of efficacy This research was performed in order to identify medical students learning styles in 2007 Methods : In this descriptive study a questionnaire including demographic questions and Kolb Learning Style Inventory was distributed amongst all medical students who were attending the first semester of 2007 in Birjand University of Medical Sciences This tool allows classification of learning styles into 4 groups: converging accommodating assimilating and diverging Results : Among 267 distributed questionnaires 175 were filled by students 68 percent of students were female mean (±SD) age of the students was 22(±25) and their grade point average was 165(±15) The most prevalent learning style was converging (52%) followed by assimilating (286%) diverging (97%) and accommodating (97%) There was no significant relationship between learning style and age sex educational level and grade point average Conclusion : Considering that people with converging learning style are competent in solving problems it necessitates that teachers at universities change their traditional methods into new ones like Problem Base Learning (PBL) and Evidence Based Medicine (EBM) so that they help students learn immense medical information